Electrophoretic Deposition of Carbon Nanotubes and Bioactive Glass Particles for Bioactive Composite Coatings - Schausten, M. Charlotte; Meng, Decheng; Telle, Rainer; Boccaccini, Aldo R. (Ceramics International, 2010)
The production of bioactive coatings consisting of 45S5 Bioglass® and mutli-walled carbon nanotubes (CNTs) by electrophoretic deposition (EPD) was investigated. In addition to pure Bioglass® coatings, the co-deposition and sequential deposition of Bioglass® particles (size <5 μm) and CNTs on stainless steel substrates were carried out in order to fabricate bioactive, nanostructured composite layers. The optimal experimental conditions were determined using well-dispersed suspensions by means of a trial-and-error approach by varying the relevant EPD parameters: applied voltage and deposition time. SEM images demonstrated the successful fabrication of Bioglass®/CNT composites by revealing their morphology and topography. The co-deposition of Bioglass® particles and CNTs resulted in homogenous and dense coatings exhibiting the presence of well-dispersed CNTs placed in-between micron-sized Bioglass® particles. This network of high-strength CNTs embedded in the glass layer could act as reinforcing element leading to higher mechanical stability of the coatings. The coatings obtained by sequential deposition offered a two-dimensional nanostructured fibrous mesh of CNTs covering the Bioglass® layer thus providing a controlled (ordered) nano-topographical surface. This surface nanostructure has the potential to promote the attachment and growth of osteoblast cells and to benefit the formation of bone-like nanosized hydroxyapaptite crystals in contact with body fluids. © 2009 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.electr
Keywords: Bioactive glass; Biomaterials; Carbon nanotubes; Electrophoretic deposition